Caminhos do desenho: arte e jogo na construção de imagens - Dantas, Luiz Elson (2021)
This research focuses on the production and execution of pedagogical proposals, from the report of two experiences of creating a board game, analyzing how the didactic strategies present in the dynamics of games can contribute to the improvement of the teaching of drawing in arts classes. In this way, the research seeks to verify how the mechanics of the games can stimulate and expand the interest of students in the study of drawing, through practical activities and reflection on the development of their personal graphics. For this, he walks through bibliographic sources that discuss the development of children's drawing in different perspectives, such as Lowenfeld, Luquet, Coutinho, Guimarães, Pillar and Iavelberg, and finds in theories about games (Huizinga) and in researchers of the theme (Kishimoto, Tavares, Petry) support to bring the drawing closer to the characteristics of the game. In the construction of the games it relies on the aesthetics of Pareyson's formactivity and the Csikszentmihalyi flow concept. During the planning and development of the games, a certain path developed as an affective cartography was built, represented by drawings produced by the students, which reflect their identities, their tastes, their values and feelings. The research concludes by reaffirming the importance of ludicity for the development of personal graphics and exposes the evidence of the work carried out in digital journals published in a blog, in addition to a pedagogical proposal presented in the form of comics and in this dissertation.